Migration bewegt und bildet Kontrapunktische Betrachtungen - Böttcher, Alexander; Hill, Marc; Rotter, Anita; Schacht, Frauke; Wolf, Maria A.; Yildiz, Erol (innsbruck university press, 2019)
The contrapuntal readings practiced in the present volume, which are based on different ways of thinking and seeing reality, call into question the sorting and classifications practiced up to now. Migration is not degraded to a collaborative research centre, but is rather seen as a social analysis and placed at the centre of scientific considerations. The focus is on approaches and ideas in which historical developments and global changes are thought from the perspective and experience of migration, without however overlooking the asymmetrical power relations and structural inequalities. The Motto "Migration moves and forms" expresses this attitude. - Die in dem vorliegenden Band praktizierten kontrapunktischen Lesarten, die auf anderen Denkhaltungen und Wirklichkeitsauffassungen beruhen, suspendieren lang eingeübte Sortierungen und Klassifikationen. Migration wird nicht zu einem Sonderforschungsbereich degradiert, sondern als Gesellschaftsforschung betrachtet und ins Zentrum wissenschaftlicher Überlegungen gerückt. Im Mittelpunkt stehen Zugänge und Gedanken, in denen historische Entwicklungen und globalgesellschaftliche Zusammenhänge aus der Perspektive und Erfahrung von Migration gedacht werden, ohne jedoch die asymmetrischen Machtverhältnisse und strukturellen Ungleichheiten zu übersehen. Das Motto "Migration bewegt und bildet" bringt diese Haltung zum Ausdruck.